Evaluation of Nurses’ Knowledge about Evidence- Based Practice in General Hospitals at Al-Nasiriyah City, Iraq - Fawzi, Duha Ali; Qassim, Wissam Jabbar (International Journal of Psychosocial Rehabilitation, 2020)
The objectives the present study aims to find out the knowledge’s of nurses about evidence-based practices and to find out the relationship between the nurses’ knowledge toward evidence- based practice and their demographic characteristics. Methods: A descriptive study was conducted at the Imam Hussain General Teaching Hospital in Nasiriyah city from October 10, 2019 to April 10, 2020, to achieve the objectives of the present study, a simple randomized (probability sample) consists of 155 nurses was working in several departments of the hospital. The data are collected through using constructed questionnaire designed. The results: The majority of nurses are at age group (20-25) years, mainly females and the majority (63.9%) and have a diploma in nursing. The level of nurse knowledge was moderate to poor in knowledge of evidence-based practices (60.0%). There are statistical significant differences between the nurses’ knowledge and their demographic characteristics (educational level, average hours per week, years of nursing service), while there are no statistical significant differences between the nurses’ knowledge and their demographic characteristics (age, gender, job description, training courses on evidence-based practices and the workplace). Recommendations: The study was recommended that the Ministry of Health (MOH) should play a key role in attention to training courses on evidence-based practices. In addition, evidence-based practices should be included in the nursing curriculum for students in order to disseminate the basis of this practice, and provide scientific books and journals about evidence-based practice to the nursing team in the hospitals.